New Tweakable Block Algorithm - Julakidze, Levani; Kochladze, Zurab; Kaishauri, Tinatin (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Modern cryptography is the cornerstone of computer and communications security. Its foundation is based on various concepts of mathematics such as number theory, polynomial algebra, probability theory, etc. In the paper, original method for construction of the new symmetric algorithm is presented and described. In order to obtain the method the appropriate material has been elaborated on: symmetric cryptosystem and tweakable block ciphers. In modern cryptography symmetric block ciphers, which are constructed based upon the principles of the classic cryptography, are irreplaceable while transferring large amounts of confidential information in the open channel. At the same time their capacities are limitless to the extent that it is possible to use them for various cryptographic constructions. General fault of the ciphers is their determination. In order to correct this fault today there are already existing so-called tweakable block ciphers. This direction is the news of the modern cryptography. In our paper the problem of construction of such cipher is overviewed by means of the Hill method. As it is known, Hill algorithm is one of the best methods to achieve diffusion. General attention in the paper is driven to realization of Hill algorithm in the way that, it is fast and presents necessary characteristic of the symmetric algorithm.